Does Population Density have Any Effect On Entrepreneurial Rates? Evidence From US Counties - Karahan, Hatice (Journal of Social and Development Sciences, 2013)
Inspired from the theory of division of labor, I test the hypothesis that self-employment rate declines with a greater density of the population. The motivation is the existence of a huge variation of population densities and a considerable difference in self-employment rates across US states and counties. Results show that a negative and statistically significant impact of population density is present. Hence, people who are located in less crowded areas are more likely to be self-employed. Considering the relatively low availability of good-matching jobs in smaller places, self-employment can be explained as a failure of the size of the market place.